(untitled) (Journal Of Educational and Psychological Researches, 2025)
The current research aims to identify the effect of the hands-and-minds strategy on the achievement of dictation material among second-year middle school students. To achieve this goal, the researcher adopted the experimental method. The research sample consisted of 70 students, 35 students as the experimental group and 35 students as the control group who studied using the traditional method. The researcher conducted a statistical equivalence between the students of the two research groups in the following variables: the chronological age of the students calculated in months, the academic achievement of the parents, and the Arabic language grades for the previous year, the Hanmon Nelson test, and the pre-administration test for the two study groups. The researcher developed the achievement test, which consisted of 14 multiple-choice items and 6 items of the essay test. The researcher used the Chi-square test for two independent samples, the T-test for two samples, the difficulty coefficient, the discrimination coefficient, the effectiveness of the wrong alternatives, and the statistical bag (SPSS). The results showed that there is a statistically significant difference between the experimental and control groups in the achievement test in favor of the experimental group. The researcher recommended encouraging Arabic language teachers to use modern methods and strategies in teaching and holding training courses for teachers on using various teaching methods and going beyond the norm. The researcher suggested conducting studies on the effect of the hands-and-minds strategy on the branches of the Arabic language.